2019
DOI: 10.1111/jch.13755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐existing hypertension and control status before atrial fibrillation onset on cardiovascular prognosis in patients with non‐valvular atrial fibrillation: A real‐world database analysis in Japan

Abstract: Hypertension is an important risk factor for non‐valvular atrial fibrillation (NVAF) and its prognosis. However, there is no study to clarify the impact of pre‐existing hypertension and BP control status before the onset of AF on the prognosis after the onset of AF. This retrospective real‐world cohort analysis used data from the Japan Medical Data Center Co., Ltd database. The presence of NVAF and hypertension, plus the occurrence of adverse events, was based on ICD‐10 codes in the database. The primary compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…2 Hypertension is one of the major etiologic factors for coexisting AF, and blood pressure (BP) control is important for the prevention of AF. 3,4 Aging can increase the risk of developing both hypertension and AF, and coexisting AF and hypertension can increase stroke risk. 5 A new method for diagnosing AF in hypertensive patients is thus urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Hypertension is one of the major etiologic factors for coexisting AF, and blood pressure (BP) control is important for the prevention of AF. 3,4 Aging can increase the risk of developing both hypertension and AF, and coexisting AF and hypertension can increase stroke risk. 5 A new method for diagnosing AF in hypertensive patients is thus urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…As in the present substudy, based on the average of morning and evening home blood pressure, HONEST study patients had insufficient control of morning H‐SBP. Patients with severe masked hypertension in the HONEST study were older, had cardiovascular comorbidities, and lower BMI 8 . A Finnish study evaluating similar associations also found that older age and current smoking were independent predictors of masked hypertension 49 .…”
Section: Discussionmentioning
confidence: 80%
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%